PENGARUH SALES GROWTH, OPERATING CASH FLOW, DAN PROFIT GROWTH TERHADAP FINANCIAL DISTRESS PADA PERUSAHAAN NON-CYCLICAL FOOD AND BEVERAGE YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2021-2023 - Bagus, Andika; Mansur, Fitrini; Hernando, Riski (Magister Ilmu Akuntansi Universitas Jambi, 2025)
This study aims to examine the effect of profitability, liquidity, and leverage on financial distress by testing each variable individually. Specifically, this research analyzes (1) sales growth, (2) operating cash flow, (3) profit growth, and (4) financial distress in companies operating in the Non-Cyclical Food and Beverage (F&B) sector listed on the Indonesia Stock Exchange (IDX). The population consists of 72 companies listed on the IDX from 2021 to 2023. The data used are secondary data, and the analysis was conducted using descriptive statistics and hypothesis testing with multiple linear regression and the Random Effect Model approach. The findings show that partially, sales growth and operating cash flow have no significant effect on financial distress, while profit growth has a significant effect. These findings are consistent with signaling theory, which posits that a company’s financial information can serve as either a positive or negative signal to investors when assessing the likelihood of corporate bankruptcy. This study is expected to serve as a valuable reference for management and investors in identifying and mitigating financial distress risks in the future.